Sistem Informasi Geografis (SIG) Pemetaan Wilayah Transmigrasi Dinas Tenaga Kerja Dan Transmigrasi Provinsi Sumatera Selatan - Irman Effendy; Dinda fahmilia (BETRIK, 2025)
This study develops a web-based Geographic Information System (GIS) for mapping transmigration areas at the Manpower and Transmigration Office of South Sumatra Province. The main problem addressed is manual, unintegrated data management with limited spatial visualization. An applied research approach using the Waterfall development model was employed. The system was built using PHP, MySQL, and Leaflet.js. The results show that the system improves data management efficiency, accelerates reporting, and supports spatial data–based decision making. The novelty of this study lies in the integration of spatial and non-spatial transmigration data into a centralized WebGIS equipped with automated reporting and transparent information access at the regional government level. The system was validated through functional testing and user evaluation and is considered suitable for implementation.